A Revised Multifamily Group Curriculum: The Need for Family Member Recovery from Addiction. Issue 4 (2nd October 2017) - Shumway, Sterling T.; Schonian, Sarah; Bradshaw, Spencer; Hayes, Nicholas D.
ABSTRACT: This article presents a revised curriculum for a family program developed for family members who are participating in a family program at a residential treatment for addiction. The article consists of a comprehensive overview of the modules developed for the program, inclusive of multifamily groups, psychoeducational components, and other family therapy modalities. In addition, preliminary results are presented demonstrating the positive effects of the program, while simultaneously building a foundation for the development and necessity of family member recovery.